Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm trying to find a recurrence relation for the coefficients for the Maclaurin series for $\tan(x)$ by substituting $y=\sum_{k=0}^{\infty}C_{2k+1}x^{2k+1}$ into the differential equation $y'=1+y^2$. This is because $\tan(x)$ is the solution to the initial value problem for the aforementioned DE with the initial condition $y(0)=0$; this is also where the form $\sum_{k=0}^{\infty}C_{2k+1}x^{2k+1}$ comes from (the fact that $\tan(x)$ is an odd function and that $y(0)=0$ which implies $C_0=0$). But I have no clue how to work "around" the expression $y^2=\big(\sum_{n=1}^{\infty}C_{2k+1}x^{2k+1}\big)^2$. How can I find a recurrence relation with an infinite squared summation? Any help is appreciated, thank you.

share|improve this question
    
The coefficients will get convolved i.e. $(\sum_{k\ge0}C_kx^k)^2=\sum_{k\ge0}(\sum_{i=0}^kC_iC_{k-i})x^k$. –  sai Apr 30 '12 at 0:11
add comment

1 Answer 1

up vote 4 down vote accepted

Take the Cauchy product:

$$\begin{align*} \left(\sum_{k\ge 0}C_{2k+1}x^{2k+1}\right)^2&=x^2\left(\sum_{k\ge 0}C_{2k+1}x^{2k}\right)^2\\\\ &=x^2\sum_{k\ge 0}D_{2k}x^{2k}\;, \end{align*}$$

where $$D_{2k}=\sum_{i=0}^kC_{2i+1}C_{2(k-i)+1}\;.$$ Thus, the differential equation becomes

$$\begin{align*} \sum_{k\ge 0}C_{2k+1}(2k+1)x^{2k}&=1+x^2\sum_{k\ge 0}\sum_{i=0}^kC_{2i+1}C_{2(k-i)+1}x^{2k}\\ &=1+\sum_{k\ge 1}\sum_{i=0}^{k-1}C_{2i+1}C_{2(k-i)-1}x^{2k}\;, \end{align*}$$

and we have $C_1=1$ and $$C_{2k+1}=\frac1{2k+1}\sum_{i=0}^{k-1}C_{2i+1}C_{2(k-i)-1}$$ for $k\ge 1$.

E.g.,

$$\begin{align*} C_3&=\frac13 C_1^2=\frac13\;,\\ C_5&=\frac15(2C_1C_3)=\frac2{15}\;,\text{ and}\\ C_7&=\frac17(2C_1C_5+C_3^2)=\frac{17}{315}\;. \end{align*}$$

share|improve this answer
    
In other contexts, the coefficients of the squared function would be what is termed a self-convolution, or autoconvolution. –  J. M. Apr 30 '12 at 0:41
    
Say we have $\big(\sum_{i=0}^{n}a_i\big)\big(\sum_{j=0}^{n}b_j\big)$ $=a_0\big(\sum_{j=0}^{n}\big)+a_1\big(\sum_{j=0}^{n}\big)+...+a_n\big(\sum_{j=0}‌​^{n}\big)$ which equals $\sum_{i=0}^{n}\sum_{j=0}^{n}a_ib_j$. Why do we shift the index of the second summation? –  Hautdesert Apr 30 '12 at 1:39
    
@Hautdesert: I don’t understand. This example is very different from the product of two series (or for that matter two polynomials), and I don’t know what index you think is being shifted. –  Brian M. Scott Apr 30 '12 at 1:44
    
@BrianM.Scott: Is the reasoning in my previous comment not a generalization of the product of two arbitrary polynomials? I thought we could just set $a_i=c_ix^i$ and derive the Cauchy product. –  Hautdesert Apr 30 '12 at 1:49
    
@Hautdesert: Not if you want to group the product terms according to powers of $x$ so as to be able to match coefficients in $y'$ and $1+y^2$. That’s why the coefficient $D_{2k+1}$ of $x^{2k}$ above is itself a sum of products. Similarly, in $(a+bx+cx^2)(d+ex+fx^2)$ the coefficient of $x^3$ is $bf+cd$, since there are two $x^3$ terms. –  Brian M. Scott Apr 30 '12 at 1:55
show 2 more comments

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.